2014
DOI: 10.1007/s00484-013-0761-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of transpiration to rain pulses for two tree species in a semiarid plantation

Abstract: Responses of transpiration (Ec) to rain pulses are presented for two semiarid tree species in a stand of Pinus tabulaeformis and Robinia pseudoacacia. Our objectives are to investigate (1) the environmental control over the stand transpiration after rainfall by analyzing the effect of vapor pressure deficit (VPD), soil water condition, and rainfall on the post-rainfall Ec development and recovery rate, and (2) the species responses to rain pulses and implications on vegetation coverage under a changing rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 87 publications
6
33
0
Order By: Relevance
“…Yang et al (2008) indicated that in the semiarid Loess Plateau, P. tabulaeformis uses water more efficiently than R. pseudoacacia, and Malus pumila. Similar results were found in mixed forests of different ages (Chang et al, 2013) and different species (Chen et al, 2014b;Nie et al, 2005). In dry regions, P. tabulaeformis might be a good drought-resistance species that could help control soil loss and improve the ecological environment.…”
Section: Implications Of This Studysupporting
confidence: 76%
See 1 more Smart Citation
“…Yang et al (2008) indicated that in the semiarid Loess Plateau, P. tabulaeformis uses water more efficiently than R. pseudoacacia, and Malus pumila. Similar results were found in mixed forests of different ages (Chang et al, 2013) and different species (Chen et al, 2014b;Nie et al, 2005). In dry regions, P. tabulaeformis might be a good drought-resistance species that could help control soil loss and improve the ecological environment.…”
Section: Implications Of This Studysupporting
confidence: 76%
“…Sap flow reduction caused by stomatal closure is considered to be the preliminary response of canopy transpiration to water stress. When water is sufficient during the rainy days, the parameter of vapor pressure deficit (VPD) can determine the transpiration amount (Chen et al, 2014b). However, transpiration is restricted by the plant's hydraulic conductance capacity and cannot exceed the total water amount obtained from the soil.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is supported by our observation that (i) 90% of the fine roots were within the upper 50 cm of the soil; (ii) the rooting density at soil depths >50 cm was very low (1 to 2 fine roots per dm 2 ); and (iii) soil moisture changes at the soil depths of 80 and 100 cm were less than 3 vol % during the balanced period. Similar soil water depletion patterns of black locust were observed by other studies [30,40]. Chen et al [30] measured soil moisture of black locust at the depth of 0-25 and 75-100 cm.…”
Section: Diurnal Cycle Of Transpiration Estimated Using Granier's Orisupporting
confidence: 72%
“…Similar soil water depletion patterns of black locust were observed by other studies [30,40]. Chen et al [30] measured soil moisture of black locust at the depth of 0-25 and 75-100 cm. They found insignificant soil moisture variations in the deeper soil during the vegetation season.…”
Section: Diurnal Cycle Of Transpiration Estimated Using Granier's Orisupporting
confidence: 72%
“…In China, there has been an increasing research focus on the sap flow characteristics in arid and semi-arid regions, where soil water is limited [39][40][41][42]. Many people think that water shortage problems only exist in arid or semi-arid regions.…”
Section: Discussionmentioning
confidence: 99%